Integration of Amaedola in Pastoral Context of the Catholic Church in Nias, Indonesia - Hulu, Stefanus Deliati; Daeli, Onesius Otenieli (FOCUS, 2025)
This study aims to reaffirm the relevance of amaedola, a traditional proverb of Nias which is rich ofethicsand moral values, as a means to form a humanistic, integrative, and dignified character. Despite its deep cultural significance, amaedolais increasingly neglected, particularly among younger generations who are more captivated by the allure of global culture. The rapid flow of information and modern technology has further eroded interest in local wisdom. This research employs a qualitative methodology with an ethnographic approach. Data were collected through literature review, interviews, and direct observation in local communities. The findings reveal that amaedolaserves as an effective medium for pastoral engagement in Nias, as its messages and meanings are embedded in the communal psyche and resonate with the lived experiences of the people. These values facilitate a more accessible embodiment of faith and spirituality through existing cultural traditions. The study implies that integrating amaedolainto pastoral practices not only enhances cultural sensitivity in ministry but also contributes to the preservation and revitalization of Nias’ indigenous wisdom. The originality of this research lies in its contextual theological approach, which bridges local culture and pastoral praxis in a manner that affirms indigenous identity and spiritual development.